Karakteristik Fisik Edible Film Pati Jagung (Zea mays L) Termodifikasi Kitosan dan Gliserol - Ihlana Nairfana; Muhammad Ramdhani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
Edible film is a thin layer that is used as a substitute for synthetic plastic or used as a primary packaging of food product. Corn starch that is suspended with chitosan and glycerol is able to improve the quality of edible film. The purpose of this research is to determine the physical characteristics of edible film from modified corn starch. The concentrations of chitosan used were 15%, 20% and 25%, and glycerol were 30% and 40%. Physical characteristics of edible film observed were thickness, absorption, solubility and film degradation. The thickness of the film ranges between 0.06-0.14 mm. The best treatment for film absorption, solubility and degradability is obtained from the addition of 15% chitosan and 40% glycerol, whilst the lowest was from 25% chitosan and 30% glycerol. plastics, thickness, absorption, solubility